Design of a ground compatible input stage folded Cascode CMOS Op-Amp with class AB rail-to-rail output stage - Sun, Xuan (Nanyang Technological University, 2024)
In the digital era, signal processing is an essential function in Internet of Things (IOT) and Artificial Intelligence (AI). This project involves a Ground Compatible input stage Folded Cascode CMOS Op-Amp with Class AB Rail-to-Rail output stage. The Op-Amp is suited for a large number of signal processing functions such as filtering and amplification of signals in portable and industrial equipment. The Op-Amp has an output drive capable of 20mA minimum and Miller Compensation with Nulling Resistor using 55nm CMOS technology. It is designed with a Gain-Bandwidth Product of 55.73MHz with a supply of 1.8V under typical conditions. It has an Open-Loop Gain of 84.69dB, Common Mode Rejection (CMR) of 89.88dB at 1kHz and Power Supply Rejection (PSR) of 59.11dB at 1kHz. The Total Harmonic Distortion is 1.055%.